Conflicting ethical issues in dentistry - Akram, Afrah (International Journal Of Community Medicine And Public Health, 2023)
Dentists, like any other profession that deals with human rights and liberties, owe a duty to their patients and the communities in which they practice. The American Dental Association's (ADA) code of dental ethics provides a standard to which all dental professionals are expected to comply. It emphasizes that each dental professional is accountable for "maintaining and strengthening" their profession. There are set rules for this, and all dentists should follow these principles when performing their duties to patients, the public, the profession, and their colleagues. This article focuses on the fundamental principles of ethics and conflicts among them.